MENINGKATKAN ERP-EFFICACY MAHASISWA PSIKOLOGI MELALUI ODOO HUMAN CAPITAL TRAINING - Bantam, Dian Juliarti; Fahmie, Arief; Zulaifah, Emi (JURNAL PSIKOLOGI INSIGHT, 2019)
This reserach examined the effect of Odoo Human Capital Training (OHCT) to improve ERP-Efficacy of psychology students. The reasearch is an intervention to improve efficacy about ERP softwares. This research used classroom action research (CAR) method of quasi experimental type with nonequivalent control group with pretest and posttest design. The participants were 35 students, with 18 students assigned to experimental group and 17 students to control group. The experimental group was trained for 4-5 hours each day within two days. The ERP-Efficacy was mesured by the ERP-Efficacy Questionnaire (ERPEQ) using 3 aspect from Compeau dan Higgins (1995). The aspect are ERP magnitude, ERP strength, and ERP generalizability. The data were analyzed by using anava mixed design. The result showed there was a significant difference of ERP-Efficacy between experimental and control group for pretest, posttest and follow up observations, with a value of F (37.25) and p (0.000). These hypothesis of this research that the effect of OHCT can improve the ERP-Efficacy among psychology students were accepted.